Salmonella daarle and Salmonella hiduddify associated with acute gastroenteritis in piglets in India (Microbes and Health, 2017)
The present study was conducted to investigate an acute gastroenteritis outbreak in an unorganized pig farm in the North Eastern Hilly Region of India. Fecal samples were collected from 20 pigs including 5 piglets, which were suffering from acute gastroenteritis and were processed for detection of E. coli, Salmonella, Clostridium sp., Rotavirus, Picobirnavirus as well as parasitic eggs and larvae by standard laboratory techniques. Virulence genes for pathogenic E. coli and Salmonella were detected by specific PCR assays. A total of 77 E. coli were isolated, all of which were found to be negative for any putative virulence genes of STEC/VTEC, ETEC, EHEC and EPEC pathotype by PCR. A total of 5 salmonellae were also isolated from 5 affected piglets, of which 1 and 4 were recorded as Salmonella daarle and Salmonella hiduddify, respectively. All the Salmonellae were positive for enterotoxin (stn) and invasion (invA) genes by PCR. In conclusion it may be stated that this is the first report of S. daarle and S. hiduddify associated with piglet diarrhoea and also first report from India with any type of enteric infection in man and animalsMicrobes and Health, December 2016, 5(1): 1-3